Tells with Isrâliîyyât: The Story of Harut and Marut in the content of Tafsir Bil-Matsur - Prakoso, Theo Jaka (Universitas Islam Negeri Alauddin Makassar, 2020)
Isrâ'îliyyât stories through speakers from Jewish and Christian scholars who have converted to Islam. They told a lot when describing the stories contained in the Koran, including the story of two angels Harut and Marut, who became polemic among mufassir. So the approach taken in the study is to trace back various histories based on those listed in the main book of interpretation bil'matsur. Al-the results of this study reveal that the existence of Isrâ'îliyyât's history is considered dangerous, mainly if it is used by laypeople who are unable to understand and know whether or not it is valid. In it, there are many khurafat or stories of prophets or others that are illogical and able to shake one's faith. However, the Isrâ'îliyyât stories are justified as long as they do not contradict the Qur'anic texts and authentic traditions.